THE EFFECT OF ISLAMIC FINANCIAL LITERACY, RELIGIOSITY, SERVICE QUALITY AND PROMOTION TO INTEREST OF SAVING CUSTOMERS IN ISLAMIC BANKS - Bambang Sugiharto; Icih Icih; Asep Rizal (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2022)
This study aims to determine the effect of Islamic financial literacy, religiosity, service quality, and promotion on customer interest in saving at Islamic banks. The subjects in this study were customers of Bank Syariah Indonesia (BSI) KCP Subang. The sample used in this study was 115 respondents. The sampling technique is done by probability sampling. Data collection techniques in the form of questionnaires and documentation. The method used is quantitative. The data analysis technique used in this research is logistic regression. The results of this study indicate that the Islamic financial literacy variable has a positive and significant effect on customers' saving interest, religiosity has a positive and significant effect on customers' saving interest, service quality has a negative and significant effect on customers' saving interest, while promotion has no significant effect on customers' saving interest